Cajal’s legacy in the digital era: from neuroscience foundations to deep learning - García-Lorenzo, Marcos; Herreras, Oscar; DeFelipe, Javier (Frontiers in Neuroanatomy, 2025)
Santiago Ramón y Cajal’s pioneering work laid the foundations for modern neuroscience and continues to impact the development of artificial intelligence, particularly deep learning. His neuron theory, the principle of dynamic polarization, and his insights into brain plasticity and network organization have significantly influenced both our understanding of the nervous system and the design of artificial neural networks. This article reviews Cajal’s key contributions, explores their role in the evolution of AI, and emphasizes the enduring links between neuroscience and machine learning in the digital era.